Novel routes for recycling of polyethylene terephthalate with supercritical carbon dioxide and microwaves - Hopkins, Bradley (2025)
Reliance on plastic by society has resulted in large volumes of waste requiring treatment. Often, this waste is disposed of in ways that harm the environment or prevent the re-use of the material, such as landfill or incineration. Therefore, the plastic value chain is often described as being linear because of the poor end-of-life strategies currently in place.